AN EXAMINATION AND CRITIQUE OF THE OBJECTIFICATION STEREOTYPE PORTRAYAL OF WOMEN IN TELUGU MOVIES - Yasoda Rani, B. (International Journal of Psychosocial Rehabilitation, 2024)
Movies are the media’s most potent instrument, and they are not exempt from the social conventions and practises that they reflect. It establishes the tone of our society’s narratives and reveals how much significance place on it. Traditionally, women’s roles were limited to that of homemaker, but as technology has advanced, so has the depiction of women in films, and this has had a significant impact on how society views women. The society’s ideals are influenced by the portrayal of women in films. As a Feminist, you are defined by your appearance, your traditions, and your cultural behaviour. In most movies, however, women have mostly played ornamental or glamorous roles, naughty playgirls, unpleasant conduct, and premarital sex. This is a problem. Most people’s cultural behaviour would be impacted if women were depicted in this way. As this tendency continues, it will have an impact on our younger generation